Rich activated edges of hexagonal boron nitride flakes in-situ triggered by nickel nanoparticles to achieve efficient reduction of friction and wear. (1st April 2022) - Bai, Changning; Lai, Zhenguo; Yu, Yuanlie; Zhang, Xingkai; Gao, Kaixiong; Yang, Zaixiu; Zhang, Junyan
Abstract: The application of hexagonal boron nitride ( h -BN) nanosheets as lubrication additives has attracted tremendous attention due to their excellent stability and friction performance. However, the exfoliation and functionalization of h -BN nanosheets are difficult which appear to limit the practical application of them. Herein, we demonstrate that commercial h -BN flakes ( h -BNFs) can be directly used to fabricate antifriction and antiwear coatings through a simple spraying process after mixing with nickel nanoparticles (Ni NPs). The experiment results and density functional theory calculations demonstrated that Ni NPs could in-situ promote nitrogen atoms to break down from the edges of h -BNFs, forming electron deficient h -BNFs and Ni NPs, and then the electron deficient Ni NPs would adsorb oxygen to generate superoxide radicals during friction process. The as-obtained superoxide radicals can react with the electron deficient h -BNFs, and these functionalized h -BNFs can stably adsorb poly-alpha-olefins (PAO6) molecules to form antifriction and antiwear tribo-films on the stainless steel (SS) substrates. Besides, the metal-edge interaction (SMEI) between Ni NPs and h -BNFs can accelerate PAO6 molecules converting into carbon based films on the counterpart. Fantastically, the antifriction and antiwear performance of SS have been greatly improved after coated by Ni/ h -BNF composite coatings with PAO6, with friction coefficients (COFs) as low as 0.07 and wear rates less than 1.5 × 10 −13  m 3 /(N·m), respectively. This finding opens up a new way for the practical application of commercial h -BNFs as low friction lubricants. Graphical abstract: Image 1 Highlights: The Ni/ h -BNF coating composites with PAO6 to reduce friction, thereby omitting the preparation of functionalized h -BNNSs. This method can match various lubricating oils and yield a good adhesion between coating and substrate. The role of the interfacial electronic effects between Ni and h -BNFs is revealed. The enhanced catalytic activity of the Ni/ h -BNF composite coating is identified.